Towards a Model Based Electronic Nursing Record - Jansen, Niels (American Medical Informatics Association, 2012)
The electronic nursing record (ENR) as part of the larger electronic health record has been discussed for years. Its implementation is not that widespread as often considered. E.g. in the Netherlands, a fraction of hospitals uses it. This paper describes a nurse led project in a Dutch hospital where an electronic nursing record system has been defined, based on requirements analysis, standardization through Detail Clinical Models (DCM), and implementation. Standardization of data with DCM is a method and a format to organize clinical knowledge, concepts, and data elements such that managing and exchanging semantics of data is independent from specific technology. 28 DCM are used in the specifications of the ENR. Using the DCM standards approach and the mapping of data elements to professional terminologies enable a vendor to develop what is needed for quality care, rather then sell a fixed set product.